PENEGAKAN HUKUM TINDAKPIDANA TERHADAP KERUSAKAN FISIK DAYA TARIK WISATA DALAM RANGKA MEWUJUDKAN ASAS KELESTARIAN DAN BERKELANJUTAN KEPARIWISATAAN - Duwi Cut Diana Putri; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Tourism is a dynamic activity that involves many people and enlivens various fields of business. In national development, tourism is one of the fields that contributes significantly to the country's foreign exchange apart from the oil and gas sector, plays a role in expanding employment, encouraging and equitable regional development, increasing the welfare and prosperity of the people. Supervision of the threat of environmental destruction and pollution of tourist objects is an important aspect in maintaining and preserving tourism objects as national assets in contributing to national development in the form of providing employment and other economic activities as well as foreign exchange income for a country.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem examined. This research is in the jurisdiction of Pekanbaru City. While the population and sample are the whole parties related to the problem examined in this study. Sources of data used, primary data, secondary data, and tertiary data, data collection techniques in this study with interviews and literature review.In the results of the research problem there are two main points that can be concluded, first, the supervision of the threat of damage and pollution of attractions is an important aspect in preserving tourism. The second obstacle in law enforcement is that the perpetrators of tourism fission damage are influenced by several factors; legal factors, legal relief factors, facilities and facilities factors, and cultural factors.Keywords: Law Enforcement Criminal Tourism